PENGEMBANGAN BAHAN AJAR INOVATIF BAHASA INGGRIS PROGRAM LINTAS MINAT KELAS X SMA DENGAN PENDEKATAN PRAGMATIK - Mulyani Mulyani (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2020)
The quality of English learning in high schools (SMA) needs to be improved to achieve better target competencies. One effort that can be taken is to improve the quality of teaching materials. From a number of instructional materials or textbooks of English language, it seems that improvements still need to be made, especially related to the pragmatic elements contained in the textbook. Teaching materials that present a pragmatic approach are still very limited.This study aims to find out about the forms of English language teaching materials and develop them with a pragmatic approach in order to improve the quality of learning. The research method used is research and development. Data collection techniques used in this study through observation, in-depth interviews, and questionnaires. Research development procedures include information gathering, planning, developing initial product forms (product design), field testing, and product revisions. Analysis of the data used is qualitative and quantitative analysis.The results of this study in the form of findings about the form of cross-interest program teaching materials for high school students tend to use the Englis To Pathway Specialization Program written by M. Sudarwati and Eudia Grace published Erlangga Publishers. The results of the development of English teaching materials in the cross-interest class X program with the pragmatic approach emphasize on systematic: (a) basic competence, (b) social function, teaching and learning activities, (c) topic, (d) linguistic element, (e) definition, (f) exercise / assignment, and (g) pragmatics corner.Development of English language teaching materials is dynamic. Therefore, it requires further research in the field of English for specific purposes, especially teaching materials for cross-interest programs for science and social studies programs in high school.